The Reception of The Qur’an in The Preservation Tradition of Javanese Kris - Farid Hasan; Putra Sany, Ulfi; Muhammad Kholil Ridwan (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
This study examines how Javanese Muslims integrate Qur’anic reception into the ritual care and preservation of the Kris. While the Kris has shifted from being a weapon to a symbolic object of art and cultural heritage, its preservation remains deeply intertwined with religious meaning. Within Javanese Muslim communities, Qur’anic recitation accompanies rituals surrounding the Kris, transforming it into a medium for embodying Islamic values. Using qualitative methods, this research examines how such practices localize scripture through material culture. The findings identify three typologies of Qur’anic reception: (1) Exegetical reception, encompassing ḥabl min Allāh (relation with God), ḥabl min al-nās (ethical relations with others), and ḥabl min al-‘ālam (ecological consciousness); (2) Aesthetic reception, manifested in the Kris’s tayuhan (decorative form), symbolizing humility and moral refinement; and (3) Functional reception, where the Kris serves as a medium for balance and harmony in life. By examining the Qur’an within the context of cultural practice, this study enriches the discourse on Qur’anic reception and hermeneutics. It contributes to scholarship on Islam in Southeast Asia by demonstrating how cultural artifacts, such as the Kris, preserve and embody religious meaning beyond textual exegesis. The Qur’anic receptions embodied in the preservation of the Kris reflect discursive meanings and performative engagements with the Qur’an that transcend its textual interpretation.